Do fiscal rules constrain fiscal policy? A meta-regression-analysis - Friedrich Heinemann; Marc-Daniel Moessinger; Mustafa Yeter (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2016)
We implement a meta-regression-analysis for the budgetary impact of numerical fiscal rules. Based on 30 studies published in the last decade, we offer a consensus estimate with respect to the level of statistical significance, provide suggestive evidence for the effect size, and identify study features of relevance for the measured impact of fiscal rules. Overall, the results document a constraining impact of rules. However, this impact is weakened if refined identification strategies are employed. Moreover, the results provide evidence for a publication bias in which journals are more likely to report constraining and statistically significant effects compared to working papers. We further provide recommendations for future research on the budgetary impact of fiscal rules.
urn:nbn:de:bsz:180-madoc-409042
Keywords: H50; H6; H63; 330; fiscal rules; meta-regression-analysis; public finances